Reactivity of Ammonia in 1,2-Addition to Group 13 Imine Analogues with G13–P–Ga Linkages: The Electronic Role of Group 13 Elements - Zhang, Zheng-Feng; Su, Ming-Der (Molecules (Basel, Switzerland), 2025)
Using density functional theory (M06-2X-D3/def2-TZVP), we investigated the 1,2-addition reactions of NH3 with a series of heavy imine analogues, G13=P-Rea (where G13 denotes a Group 13 element; Rea = reactant), featuring a mixed G13–P–Ga backbone. Theoretical analyses revealed that the bonding nature of the G13=P moiety in G13=P-Rea molecules varies with the identity of the Group 13 center. For G13=B, Al, Ga, and In, the bonding is best described as a donor–acceptor (singlet–singlet) interaction, whereas for G13=Tl, it is characterized by an electron-sharing (triplet–triplet) interaction. According to our theoretical studies, all G13=P-Rea species—except the Tl=P analogue—undergo 1,2-addition with NH3 under favorable energetic conditions. Energy decomposition analysis combined with natural orbitals for chemical valence (EDA–NOCV), along with frontier molecular orbital (FMO) theory, reveals that the primary bonding interaction in these reactions originates from electron donation by the lone pair on the nitrogen atom of NH3 into the vacant p-π* orbital on the G13 center. In contrast, a secondary, weaker interaction involves electron donation from the phosphorus lone pair of the G13=P-Rea species into the empty σ* orbital of the N–H bond in NH3. The calculated activation barriers are primarily governed by the deformation energy of ammonia. Specifically, as the atomic weight of the G13 element increases, the atomic radius and G13–P bond length also increase, requiring a greater distortion of the H2N–H bond to reach the transition state. This leads to a higher geometrical deformation energy of NH3, thereby increasing the activation barrier for the 1,2-addition reaction involving these Lewis base-stabilized, heavy imine-like G13=P-Rea molecules and ammonia.